Solar energy as a potential contributor to help bridge the gap between electricity supply and growing demand in Iraq: A review - Sulala Al-Hamadani (International Journal of Advances in Applied Sciences, 2020)
The pivotal role of electricity is as an enabler for every other sector in any economy. Adequate electricity supply is a vital input for the economic growth and in a range of key industries. Unfortunately, the electricity sector in Iraq has been an unsustainable fiscal burden on successive Iraqi governments yet it has not been able to meet the growing demand. Iraq’s electricity sector and government’s decision makers should look for a long-term solutions and strategies to meet the current and future demand, by taking important steps towards fostering a reliable, affordable, and sustainable electricity system in the years and decades to come. Also, Iraqi government and ministry of electricity in particular should understand that electricity is basic service and right of Iraqis, and many nations have overcome this kind of problem decades ago. Overcoming this problem will help refueling Iraqi economy and enable it to stand on its feet again. Renewable energy resources, and solar in particular could be part of the solution. This paper aims to highlight the importance of solar energy in Iraq as a potential contributor to help bridge the gap between electricity supply and growing demand. Also, it discusses the solar energy opportunities with challenges facing other renewable energy sources in Iraq.